Recognition organisations that evaluate agencies accrediting medical education programmes: Quis custodiet ipsos custodes?. Issue 2 (4th May 2017) - van Zanten, Marta
Abstract: The goals of agencies that accredit medical education programmes or institutions are to ensure high quality student experiences and to certify the readiness of graduates to further their training or begin practice as physicians. While accreditation provides a level of legitimacy, the agencies conducting the reviews vary in their organisation, robustness and transparency of decisions. Therefore, to enhance validity and comply with governmental or medical professional regulations, some agencies undergo external evaluations of their standards and protocols, a process commonly referred to as recognition. Recognition also provides stakeholders with unbiased and credible information on accrediting agencies and the educational institutions they accredit. The author compares six European and United States-based recognition organisations that evaluate agencies that accredit medical education to highlight similarities and differences in scope, processes and consequences of the review. These results contribute to the development of best practices and potential mutual acceptance of decisions in the global 'meta quality assurance' arena.